Gis och realtids-GPS på renar - Larsson, Mattias (2009)
This study is commissioned by the Swedish University of Agricultural Science (SLU - Department of Forest Resource Management) in coorporation with Sveaskog and Vilhelmina Norra Sami reindeer herding community. The purpose of this study is to analyse movement patterns and habitat use of reindeers during two winter seasons (2005/2006 and 2006/2007) in areas affected by forestry activities such as clearcutting. This study examines the possibilities of analysing information from Reindeer husbandry plans and forest variable data from kNN and SMD, in relation to GPS collar points from reindeers by using Geographical Information System (GIS). Lack of knowledge and understanding between the reindeer industry and the timber industry has often led to heated debates. The possibilities of using this type of technique are very interesting and could increase knowledge concerning land-use issues to different resource users. The main results from analyses comparing SMD, kNN, data about clearcuts, and GPS collar points from reindeers indicates that clearcut areas, younger forest, coniferous forest on lichen-dominated areas and areas dominated by pine was preferred by reindeers during the winter period. These results were similar during both winterseasons despite different snow and weatherconditions. Older clearcut areas (1986/2000) were more frequently used then the most recent clearcut areas (2000/2005). The reindeers used spruce-, mixed- and broadleaved forests less frequently and disproportionate to their availability. Analyses comparing Reindeer husbandry plans and GPS collar points from reindeers show that key habitat areas delineated by reindeer herders were used frequently during both winters, and considerably more frequent during the winter 2005/2006, characterized by good grazing conditions. Difficult conditions with icing of the snow pack made the reindeer disperse over larger areas during 2006/2007 with consequent less use of key habitat areas. Analysis of GIS-databases in relation to GPS collar points from reindeers ...